A Mixed Logical Dynamical Model of the Hegselmann–Krause Opinion Dynamics. Issue 2 (2020) - Bernardo, C.; Vasca, F.
Abstract: The heterogeneous bounded confidence Hegselmann–Krause (HK) model has been widely considered in the literature for describing opinion dynamics. In this paper a mixed logical dynamical (MLD) representation of the HK model is proposed. The linear MLD model provides a compact representation where the different thresholds of the agents influence functions explicitly appear into the model inequalities. Numerical experiments of the proposed model are used to analyze how consensus and clustering are influenced by different agents confidence bounds.